VISUAL GESTURE BASED AUGMENTED VIRTUAL KEYBOARD SYSTEM - Yousaf, M. H.; Habib, Hafiz A.; Hussain, F.; Rizwan, M. (The Nucleus, 2013)
This paper presents a novel enhancement in design of virtual keyboards for consumers of tablets and standard computing devices. Hand video is captured for virtual keyboard functionality. Hand video is augmented with a background keyboard and displayed on lower part of screen to provide feedback to user for seamless interaction with virtual keyboard. Hands are detected in video sequence. Finger joints trajectory based keystroke detection and recognition fused with augmented keys spatial information reveals the key pressed. Real time system is developed by integrating USB camera with tablet computer. Reliable results are experienced while a low cost system is achieved in comparison to existing virtual keyboard systems.